# Solve for b 3 3/4=8/2-3/2b

334=82-32b
Convert 334 to an improper fraction.
A mixed number is an addition of its whole and fractional parts.
3+34=82-32b
To write 3 as a fraction with a common denominator, multiply by 44.
3⋅44+34=82-32b
Combine 3 and 44.
3⋅44+34=82-32b
Combine the numerators over the common denominator.
3⋅4+34=82-32b
Simplify the numerator.
Multiply 3 by 4.
12+34=82-32b
154=82-32b
154=82-32b
154=82-32b
154=82-32b
Simplify each term.
Divide 8 by 2.
154=4-32b
Combine b and 32.
154=4-b⋅32
Move 3 to the left of b.
154=4-3b2
154=4-3b2
Rewrite the equation as 4-3b2=154.
4-3b2=154
Move all terms not containing b to the right side of the equation.
Subtract 4 from both sides of the equation.
-3b2=154-4
To write -4 as a fraction with a common denominator, multiply by 44.
-3b2=154-4⋅44
Combine -4 and 44.
-3b2=154+-4⋅44
Combine the numerators over the common denominator.
-3b2=15-4⋅44
Simplify the numerator.
Multiply -4 by 4.
-3b2=15-164
Subtract 16 from 15.
-3b2=-14
-3b2=-14
Move the negative in front of the fraction.
-3b2=-14
-3b2=-14
Multiply both sides of the equation by -23.
-23⋅(-3b2)=-23⋅(-14)
Simplify both sides of the equation.
Simplify -23⋅(-3b2).
Cancel the common factor of 2.
Move the leading negative in -23 into the numerator.
-23⋅(-3b2)=-23⋅(-14)
Move the leading negative in -3b2 into the numerator.
-23⋅-3b2=-23⋅(-14)
Factor 2 out of -2.
2(-1)3⋅-3b2=-23⋅(-14)
Cancel the common factor.
2⋅-13⋅-3b2=-23⋅(-14)
Rewrite the expression.
-13⋅(-3b)=-23⋅(-14)
-13⋅(-3b)=-23⋅(-14)
Cancel the common factor of 3.
Factor 3 out of -3b.
-13⋅(3(-b))=-23⋅(-14)
Cancel the common factor.
-13⋅(3(-b))=-23⋅(-14)
Rewrite the expression.
-1⋅(-b)=-23⋅(-14)
-1⋅(-b)=-23⋅(-14)
Multiply.
Multiply -1 by -1.
1⋅b=-23⋅(-14)
Multiply b by 1.
b=-23⋅(-14)
b=-23⋅(-14)
b=-23⋅(-14)
Simplify -23⋅(-14).
Cancel the common factor of 2.
Move the leading negative in -23 into the numerator.
b=-23⋅(-14)
Move the leading negative in -14 into the numerator.
b=-23⋅-14
Factor 2 out of -2.
b=2(-1)3⋅-14
Factor 2 out of 4.
b=2⋅-13⋅-12⋅2
Cancel the common factor.
b=2⋅-13⋅-12⋅2
Rewrite the expression.
b=-13⋅-12
b=-13⋅-12
Multiply -13 and -12.
b=–13⋅2
Multiply.
Multiply -1 by -1.
b=13⋅2
Multiply 3 by 2.
b=16
b=16
b=16
b=16
The result can be shown in multiple forms.
Exact Form:
b=16
Decimal Form:
b=0.16‾
Solve for b 3 3/4=8/2-3/2b

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top